2010
DOI: 10.1016/j.molcel.2010.02.018
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-451 Regulates LKB1/AMPK Signaling and Allows Adaptation to Metabolic Stress in Glioma Cells

Abstract: Summary To sustain tumor growth, cancer cells must be able to adapt to fluctuations in energy availability. We have identified a single microRNA that controls glioma cell proliferation, migration, and responsiveness to glucose deprivation. Abundant glucose allows relatively high miR-451 expression, promoting cell growth. In low glucose, miR-451 levels decrease, slowing proliferation but enhancing migration and survival. This allows cells to survive metabolic stress and seek out favorable growth conditions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
436
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(452 citation statements)
references
References 53 publications
15
436
0
1
Order By: Relevance
“…4 miRNA dysregulation is a common feature of neoplasia and numerous miRNAs have been characterized as oncogenes or tumor suppressors in many cancers including in glioblastoma (GBM). 3,[5][6][7][8][9][10][11] microRNA-134 (miR-134) has been implicated in the regulation of physiological and developmental processes. It was shown to promote mouse embryonic stem-cell differentiation, dendritogenesis, and stage-specific cortical development.…”
mentioning
confidence: 99%
“…4 miRNA dysregulation is a common feature of neoplasia and numerous miRNAs have been characterized as oncogenes or tumor suppressors in many cancers including in glioblastoma (GBM). 3,[5][6][7][8][9][10][11] microRNA-134 (miR-134) has been implicated in the regulation of physiological and developmental processes. It was shown to promote mouse embryonic stem-cell differentiation, dendritogenesis, and stage-specific cortical development.…”
mentioning
confidence: 99%
“…Based on these reports, we hypothesized that activation of the LKB1-AMPK signaling pathway mediates the suppressive effect of probucol on glioma cell proliferation. In fact, it has been reported that activation of LKB1-AMPK signaling induces apoptosis in human glioblastoma cells [16][17][18][19] . Here, we provide evidence of a novel molecular mechanism in which probucol activates AMPK to inhibit glioma cell growth through a 26S-proteasome-dependent signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the levels of both miRNAs were found to be markedly higher in patients in comparison with the levels in healthy control subjects. Another study also found that mature miR-451 was expressed at a higher level in glioblastoma multiforme tissues than in matched adjacent normal brain tissue (20,21). These data indicated that the expression of miR-451 was associated with disease states and was cell-specific, supporting the clinical value of miR-451 as a diagnostic biomarker in human cancers.…”
Section: Mir-451 In Cancer Diagnosismentioning
confidence: 83%
“…Early studies have also highlighted the roles of miR-144/451 in human cancers. Many studies have established that miR-451 is widely dysregulated in human malignancies, including in lung cancer (14,15), gastric cancer (16), breast cancer (17,18), glioma (19)(20)(21), and leukemia (22), indicating that miR-451 might play a critical role in oncogenesis. In this review, we focus on the noncanonical biogenesis pathway for miR-451 and its roles in erythroid differentiation.…”
Section: Introductionmentioning
confidence: 99%